MicroRNAs and extracellular vesicles in the gut: new host modulators of the microbiome?. (10th August 2021) - Du, Xiaochen; Ley, Ruth; Buck, Amy H
ABSTRACT: The gut microbiota plays an integral role in human health and its dysbiosis is associated with many chronic diseases. There are still large gaps in understanding the host and environmental factors that directly regulate the gut microbiota, and few effective strategies exist to modulate the microbiota in therapeutic applications. Recent reports suggest that certain microRNAs (miRNAs) released by mammalian cells can regulate bacterial gene expression to influence the microbiome composition and propose extracellular vesicles as one natural mechanism for miRNA transport in the gut. These new findings interface with a burgeoning body of data showing that miRNAs are present in a stable form in extracellular environments and can mediate cell-to-cell communication in mammals. Here, we review the literature on RNA-mediated modulation of the microbiome to bring cross-disciplinary perspective to this new type of interaction and its potential implications in biology and medicine. Abstract : Review and synthesis on current thinking and gaps in knowledge on how mammalian microRNAs and extracellular vesicles can directly modulate the gut microbiome.